Multi-omics pan-cancer analysis of monocyte to macrophage differentiation-associated (MMD) and its significance in hepatocellular carcinoma - Bai, Suyang; Wang, Yuping; Zhou, Yongning; Qiao, Liang (Cancer biomarkers : section A of Disease markers, 2025)
Background Malignant tumors are serious diseases that endanger human health. Therefore, it is crucial to identify markers that facilitate tumor diagnosis and prognostic assessment. Objective This study analyzed the significance of Monocyte to macrophage differentiation-associated (MMD) in various tumors from multiple perspectives, to explore the possibility of using MMD as a novel tumor marker. Methods Using the R software, an examination of MMD levels was conducted across diverse human cancers and their influence on cancer outcomes. MMD methylation, mutations, and immune infiltration analyses of various tumors were performed. A Cox regression model was used to predict the survival rates of patients with hepatocellular carcinoma (HCC). Finally, MMD expression and function were validated in Hep-3B cells. Results MMD was aberrantly expressed in diverse tumors and can predict patient outcomes. Methylation and functional enrichment studies indicated possible function of MMD in tumor progression, whereas immune infiltration data suggested its involvement in tumor immune evasion. Cox regression analysis revealed that elevated MMD levels were independent predictors of HCC patient outcomes. The quantitative real-time polymerase chain reaction (qPCR) data demonstrated high MMD levels in Hep-3B cells, and its suppression impeded Hep-3B cell growth. Conclusions MMD was abnormally expressed in various tumors and was closely associated with tumor prognosis. Thus, it had the potential to be used as a novel tumor marker.